(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Pulmonary Tuberculosis (TB) is a contagious bacterial infection that mainly involves the lungs, but may spread to other organs caused by Mycobacterium tuberculosis. To evaluate the age and gender characteristics of pulmonary tuberculosis patients as well as outcome of tuberculosis control. Materials and methods: A retrospective study was conducted at DOTS center at a tertiary, teaching hospital in the Chattogram region of Bangladesh. by evaluating the medical records of 133 patients with pulmonary tuberculosis. Age, gender, sputum smear status and Gene-Xpert test results were among the variables examined. Patients with comorbid conditions were not considered. Other information was not evaluated. Results: The male-to-female ratio in patients with pulmonary tuberculosis was 1.4:1. A large proportion of patients (44%) were in the young and reproductive age group. Approximately, one-fifth of patients were in the pediatric age group and onesixth of patients were in the geriatric age group. Conclusion: The finding suggests that two-thirds of all female smear-positive patients were of reproductive age has significant implications for tuberculosis control strategies due to increased chances of mother-to-newborn transmission. Because of the increased risk of default, difficulties, inconvenience, and the presence of other concomitant diseases, pediatric and geriatric patients are a large category. Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 38-41